Deserción académica e incidencia socioeducativa de los estudiantes de EGBS del Colegio de Bachillerato La Dolorosa, del cantón Chaguarpamba, periodo actual - Lizalde Agila, Solange Lisseth (2024)
The objective of this study is to analyze the factors that lead to academic dropout and socio-educational incidence of EGBS students at La Dolorosa High School, in the Chaguarpamba canton. The Likert scale survey was applied to the students and the results report that there are cases of academic dropout at the “La Dolorosa” school, attributed to economic, academic, health, family, emotional problems, and lack of interest in extracurricular activities, it was also determined that dropout negatively affects the socio-educational field. That is why it is pertinent to study these factors that are being experienced in this context that negatively affect the performance, development and professional process of the students, in such a way from my general perspective as a staff their intervention must be urgent and comprehensive. Furthermore, this research proposes clear and precise objectives such as theoretically and methodologically conceptualizing the main causes of academic dropout and socio-educational impact, determining the percentage of academic dropout and socio-educational impact, and finally developing a proposal for social intervention with a focus on Prevent and address academic dropout and socio-educational impact of students. Consequently, the methodology used in this research work is quantitative, because through the use of surveys it was possible to determine the percentage of academic dropouts and socio-educational incidence of the EGBS students of the La Dolorosa High School, Canton. Chaguarpamba. It is concluded that academic dropout is a present problem at La Dolorosa school, affecting the graduation rate and the academic and professional development of the student, requiring urgent intervention. Keywords: academic dropout, social intervention, students, performance